Implementation of AI Chatbot Application for Social Anxiety Problem - Melisa Dewi; Hasanul Fahmi (President University, 2023)
The past decade has witnessed the rapid development ofÂ Artificial IntelligenceÂ (AI)[1]. AI nowadays, are becoming more popular and integrated in every aspect of the world. Using Ai chatbot as a companion partner has been a thing since a few years ago, but with the development of AI, it is possible to inject personality into those chatbots now. With the increasing growth of social anxiety issues, it is possible to implement AI chatbot as a way to train social skills into people. Past researches have already created a chatbot that is solely for the purpose of depression in a one-on-one chatting environment. In order to create a working training regime, it is necessary to give the user the ability to change from a fully AI environment to slowly integrate with humans. The present paper considers the ability of personality trained AI chatbots and environment as a way to help people learn to socialize. This research aims to help provide a cheaper and reliable alternative for therapists by using AI chatbots as a guide for socially anxious people.